Проблематика підходів до визначення стадії життєвого циклу підприємства - Матюшенко, О.І. (Культура народов Причерноморья, 2013)
В статті наведено аналіз основних моделей життєвого циклу підприємства, розглянуто
основні підходи до визначення підприємства на кривій життєвого циклу, визначено їх недоліки та
переваги, запропонована схема оцінки стадії життєвого циклу підприємства, що базується на
розрахунку інтегрального показника фінансово–господарської діяльності підприємства та застосуванні
економіко–математичних моделей для визначення положення підприємства на кривій життєвого циклу. В статье представлен анализ основных моделей жизненного цикла предприятия,
рассмотрены основные подходы к определению предприятия на кривой жизненного цикла, их
достоинства и недостатки, предложена схема оценки стадии жизненного цикла предприятия. The paper presents an analysis of the basic models of the life cycle of the enterprise, on the basis of
which conclusions are drawn about the presence of contradictions in the approaches to the definition of the
organizational life cycle . The article also identified and analyzed the main factors that affect the performance of
the life cycle of the enterprise. In this study, the basic approaches to the determination on a life cycle curve,
defined by their main advantages and disadvantages. On the basis of the analysis of literary sources in the
article, a scheme assessment stage of the life cycle of the enterprise, which is based on the calculation of the
integral index of financial–economic activity of the enterprise and application of econometric models to
determine the position on a life cycle curve . The proposed method for determining the stage of the life cycle of
the enterprise allows you to apply a systematic and comprehensive approach, and also to eliminate subjectivity in the assessment. Further perspectives of the study are in the detailed design methodology for assessing the
stage of the life cycle of the enterprise.